Bioclimatic approach for rural dwellings in the cold, high Andean region: A case study of a Peruvian house - Molina, Jessica R. (2021)
This paper presents a rural exemplar house built in San Francisco de Raymina (a high Andean village 3700 masl) in southern Peru that integrates passive and sustainable solar heating techniques. A climatic analysis of this village was carried out using measurements of meteorological parameters recorded throughout a whole year. The annually averaged temperature, relative humidity and horizontal daily solar energy were 8.3 °C, 73.1% and 5.2 kWh/m2, respectively. The temperatures outside and inside the most rural dwellings are almost the same, so they do not offer any protection specially, during nights when the temperature can reach values below zero. The thermal behavior of the house was modeled with the m2m tool, and an experimental validation was carried out. With the use of m2m, it was possible to create an energy balance during the month of June 2014 (the winter cold and dry season) to determine the energy loss/gain contributions by each wall and to assess how air exchanges (the flow rates of which were deduced using an inversion approach, as they could not be directly measured) between the exterior and interior influence the thermal behavior of the whole house. Infiltration contributed approximately 48.6% of the daily energy losses, while the main solar gains were from the skylights (21.8%) and the adobe walls, which absorbed heat during the day and released heat at night. © 2020 Elsevier B.V.